ENGAGING ENGLISH LEARNERS: USING AI TO INTEGRATE LOCAL LEGENDS INTO LANGUAGE LESSONS IN WEST KALIMANTAN - Agna Plasela Rosa De Vina; Trianita Avilla; Dwi Riyanti; Yohanes Gatot Sutapa Yuliana (Wiralodra English Journal, 2025)
This mixed methods study investigates the integration of artificial intelligence (AI) in incorporating local legends into English language instruction in West Kalimantan. Using an explanatory sequential design, the research examined how AI-enhanced culturally relevant materials affect English proficiency and student engagement during a one-month intervention. The study involved 30 students from a high school in Singkawang, divided into experimental and control groups. Quantitative data collection included pre- and post-tests measuring language proficiency and engagement surveys, while qualitative data came from semi-structured interviews and classroom observations. Statistical analysis revealed significant improvement in the experimental group's language proficiency (p < .001, d = 0.85). Thematic analysis identified enhanced cultural connection, improved engagement, and positive technological integration as key factors in student success. The findings suggest that AI-driven integration of local legends enhances language acquisition and cultural awareness while fostering deeper student engagement with learning materials. This research contributes to understanding technology-enhanced culturally responsive pedagogy in language education, with implications for curriculum development and teaching practices in culturally diverse contexts. Future research opportunities include examining longer-term implementation effects and applications across different cultural settings.